Comparative Study on the Carcinogenicity of 1-Nitropyrene and Benzo (a) pyrene to the Lung of Syrian Golden Hamsters Induced by Intermittent Intratracheal Instlliations - YAMAMOTO, Akiyo; ISHINISHI, Noboru; HISANAGA, Akira; KITAMORI, Shigeji; INAMASU, Takeo (Journal of Japan Society of Air Pollution, 1987)
1-nitropyrene (1-NP), which has recently been considered to be one of the important environmental mutagens among air pollutants, and benzo (a) pyrene (B (a) P), a well known environmental carcinogen, were intratracheally instilled into male Syrian golden hamsters once a week for 15 weeks. The total dosage was 30 mg. At the same time, a further control group received only phosphate buffer solution. During the total life span, tumor incidence rates in the 1-NP and B (a) P groups were 10% and 86%, respectively, but no tumor developed in the control group. The incidence rates of lung tumors in the 1-NP and B (a) P groups were significantly different, but not in the 1-NP and control groups. These results show that the carcinogenicity of B (a) P to the lung of Syrian golden hamsters should be considered more seriously than that of 1-NP.